Arabidopsis Forkhead‐Associated Domain Protein 3 negatively regulates peroxisome division. Issue 7 (6th June 2017) - Desai, Mintu; Pan, Ronghui; Hu, Jianping
Summary: Peroxisomes are ubiquitous and dynamic eukaryotic organelles capable of altering their abundance in response to environmental and developmental cues, yet the regulatory mechanism of plant peroxisome division/proliferation is unclear. To identify transcriptional regulators of the peroxisome division factor gene PEX11b, we performed a nuclear pull‐down experiment and identified Arabidopsis Forkhead‐Associated Domain Protein 3 (FHA3) as a novel protein that binds to the promoter of PEX11b . Our data supported the conclusion that, in contrast to the previously identified HY5 HOMOLOG (HYH) protein that promotes the transcription of PEX11b, FHA3 is a negative regulator of PEX11b expression and peroxisome division. Abstract : Peroxisomes are essential and dynamic organelles capable of changing abundance through division and proliferation in response to environmental and developmental cues. This work identified an Arabidopsis transcription factor Forkhead‐Associated Domain Protein 3 (FHA3), which negatively regulates peroxisome division by repressing the expression of the peroxisome division factor gene PEX11b .